INLET CONDUIT DESIGN OF VAD BASED ON MAGNETIC RESONANCE IMAGING (MRI) OF HUMAN SUBJECT - SASAKI, E.; KINOSHITA, M.; SEKII, H.; AKUTSU, T.; TAKANO, H.; TATSUMI, E.; HODA, H.; YAGURA, A.; TAENAKA, Y. (Jinko Zoki, 1989)
Six types of inlet conduit of VAD were designed based on the anatomical data obtained from MRI of the normal individuals, mitral stenosis, and cardiomyopathy patients. A L-shaped conduit, which was bent as the configulation of the right atrium, was applicable to the insertion via the right pulmonary vein. The ventricular apex cannula needed opposite turns when the conduit was guided to the abdominal wall. A simple L-shaped conduit was applicable to the other insertion sites. These newly desighned conduits should prevent the inflow obstruction of the pump.